Inverse Method on Volume Utilization Factors of Rotor based on Average Theoretical Flow of Roots Pump - Ronghe Xiao; Yulong Li (Jixie chuandong)
In order to derive the volume utilization factors of Roots rotor for pump simply and efficiently，a novel inverse method of volume utilization factors is proposed based on the causal relationship between volume utilization factors and the average theoretical flow，and the different effects of two profile structures with and without clearance on volume utilization factors are analyzed. All results show that the inverse method from the average theoretical flow which is the effect to the volume utilization factors which are the cause is simple and efficient，the results are accurate and reliable，and the general applicability is strong； the profile structure with clearance is beneficial to maximize the volume utilization factor； by controlling the upper limit of profile factor，the shape factors and volume utilization factors are indirectly influenced by the curve type of conjugate profile； volume utilization factor can be simplified as a single variable function of shape factors，and the type of conjugate profile determined by profile factors has little influence on the volume utilization factors etc. It provides a new idea and method for calculating the volume utilization coefficient and other profile characteristics of rotor pump.